CITRA TUJUAN WISATA DAN CITRA KULINER ACEH SERTA PENGARUHNYA TERHADAP NIAT WISATAWAN UNTUK KEMBALI MENGUNJUNGI KOTA BANDA ACEH - Mohammad Ridha, Rizki Amalia (Departemen Manajemen, 2018)
Abstract: This study purpose to determine the effect of image tourism destination and image food to intention to revisit of Banda Aceh. This research methode using questionnaire as research instrument. Non probability samplin is used as a sampling technique. Analysis methods of testing and data analysis was performed using the SPSS with formulation of multiple linear regression. The results of this study indicate that image tourism destinations and image food influence intention to revisit and the image food influence the intention to revisit. Keywords: image tourism destination, food image, and intention to revisit